A refined kidney tumor nephrometry system employed to screen pediatric patients who are eligible for nephron sparing surgery - Huang, Mingchuan; Fei, Yingchun; Zhong, Zhihai; Jiang, Hong; Liu, Longshan; Liu, Juncheng; Zhang, Huanxi; Li, Jun; Xu, Zhe; Gao, Pengfei; Wang, Changxi (Frontiers in Pediatrics, 2025)
PurposeComprehension of the anatomical characteristics of pediatric kidney tumors is crucial for making surgical decisions. Previous kidney tumor nephrometry systems failed to incorporate two significant factors: tumor thrombus and multifocality. We develop a refined nephrometry system based on a comprehensive understanding of the characteristics exhibited by pediatric kidney tumors.MethodsThe TUMORS nephrometry scoring system comprises 6 indicators, including tumor (T)hrombus, (U)rinary collecting system involvement, (M)ultiple tumors, (O)utward property, (R)adius, and (S)ite relative to the polar lines. Each renal unit was assessed and scored independently. The complexity characteristics of kidney tumors were summarized, and the correlation was compared with RENAL nephrometry system. Furthermore, the complexity of kidney tumors was compared across different surgical procedures.ResultsA total of 43 patients were enrolled, involving 70 kidney units. Radical nephrectomy (RN) was performed on 13 kidneys, while the remaining 57 kidneys underwent nephron sparing surgery. In the NSS group, tumors in 37 kidneys were resected in vivo, whereas 20 kidneys underwent tumor resection ex vivo followed by kidney autotransplantation. According to the TUMORS nephrometry scoring system, there were 13, 34 and 23 kidney units classified as low, moderate and high complexity, respectively. Tumors that underwent RN or ex vivo removal exhibited higher complexity. The complications and positive margins of NSS were not statistically significant in relation to tumor complexity.ConclusionThe TUMORS nephrometry scoring system holds significant guidance for the decision of surgical protocol and can be applied to the preoperative evaluation.